Preference for Redistribution during Structural Change with Labor Mobility Frictions - Krzysztof Makarski; Joanna Tyrowicz (Institute of Labor Economics (IZA), 2022)
Thorough structural change occurs periodically across world economies. In a parsimonious overlapping generation setup with political economy, we present a novel result: structural change not only exacerbates the rise in inequality but also strengthens the preference for redistribution. Labor mobility frictions are instrumental in this mechanism.
Keywords: H10; Z1; 330; labor mobility frictions; structural change; redistribution